Comparison of genuine, generic and counterfeit Cialis tablets using vibrational spectroscopy and statistical methods - Spálovská, Dita; Pekárek, Tomáš; Kuchař, Martin; Setnička, Vladimír (Journal of pharmaceutical and biomedical analysis, 2021)
The dubious online market in phosphodiesterase type 5 inhibitors is growing on a global scale. Counterfeit medical products can represent health issues for the user and cause medical mistrust. Within this work, genuine Cialis containing the active pharmaceutical ingredient (API) tadalafil, its generics available in the Czech Republic and the Cialis tablets from questionable online pharmacies were analysed. The methods of infra-red and Raman spectroscopy were used for the identification of the counterfeit tablets and for the verification of their API and excipients. All 9 tablets from online pharmacies were counterfeit with 2 of them even containing a different API (sildenafil, vardenafil). In addition, Raman mapping was used to determine the API and excipients' distribution and, in combination with multivariate data analysis, to separate similar tablets in clusters and to identify the outliers. Scanning electron microscopy of the samples revealed that the process of a wet granulation of micronized API was used during the formulation of the tablets. This comprehensive approach of analysis can be used for advanced exploration of the dubious samples of various medical products.
Keywords: důvěra; Ramanova spektroskopie; Counterfeit Drugs; Tadalafil; Trust; padělané léky; tablety; tadalafil; Spectrum Analysis, Raman; Tablets